Implications of Organizational Culture on Job Satisfaction - Marto Silalahi; Sisca; Onita Sari Sinaga; Vivi Candra; Sudung Simatupang (International Journal on Economics, Finance and Sustainable Development, 2021)
The purpose of this study was to determine the influence of organizational culture on job satisfaction of 40 employees of the Ministry of Religion of Simalungun Regency. The results of the study found that the value of the organizational culture and job satisfaction variables had valid and reliable results, as well as that the data used had a normal distribution. For the equation results from the simple regression path, the results show Y = 26,789 + 0.666 X, which means that there is a positive direction coefficient of organizational culture on job satisfaction, while for the results of the hypothesis that organizational culture has a positive and significant effect on job satisfaction, which means that the better The value of organizational culture will result in good job satisfaction as well, and vice versa.